2010
DOI: 10.1007/s00213-010-1821-z
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis constituents modulate ∆9-tetrahydrocannabinol-induced hyperphagia in rats

Abstract: All Delta9THC compounds displayed classical Delta9THC effects on feeding, significantly increasing shortterm intake whilst decreasing latency to the first meal. We propose that the subtle adjustment to the meal patterns seen between the purified Delta9THC and Delta9THC-BDS are due to non-Delta9THC cannabinoids present in Delta9THC-BDS. These compounds and other non-cannabinoids have an emerging and diverse pharmacology and can modulate Delta9THC-induced hyperphagia, making them worth further investigation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(80 citation statements)
references
References 42 publications
5
71
4
Order By: Relevance
“…The acute feeding test in pre-satiated rats has been utilised in many previous studies in our lab to sensitively determine hyperphagic actions of pharmacological compounds, providing detailed information on both food intake and the microstructure of meal patterns (Williams et al 1998;Williams and Kirkham 2002;Farrimond et al 2010a;Farrimond et al 2010b;Farrimond et al 2012a). In vehicle-dosed rats, feeding behaviour during the test period is minimal, typically comprising one to two small meals with a total consumption of ≤1 g, occurring after 90 min (Farrimond et al 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…The acute feeding test in pre-satiated rats has been utilised in many previous studies in our lab to sensitively determine hyperphagic actions of pharmacological compounds, providing detailed information on both food intake and the microstructure of meal patterns (Williams et al 1998;Williams and Kirkham 2002;Farrimond et al 2010a;Farrimond et al 2010b;Farrimond et al 2012a). In vehicle-dosed rats, feeding behaviour during the test period is minimal, typically comprising one to two small meals with a total consumption of ≤1 g, occurring after 90 min (Farrimond et al 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…Thirty‐six pre‐satiated, male, Lister‐hooded rats received a purified, C. sativa ‐derived Δ 9 THC (hereafter purified Δ 9 THC), a synthetic Δ 9 THC and a high‐Δ 9 THC standardized botanical drug substance (BDS), similar in composition to that used in Sativex and containing a typical array of non‐Δ 9 THC pCBs (high‐Δ 9 THC BDS; all treatments were dose matched for Δ 9 THC content; 0.00, 0.34, 0.67, 1.34 and 2.68 mg/kg; p.o. ; Farrimond et al , ). Synthetic and purified Δ 9 THC administration induced classical Δ 9 THC hyperphagia in this study: the latency to the first meal was reduced and both the first hour intake and first meal duration were increased versus vehicle treatments.…”
Section: Cannabinoid‐mediated Effects Upon Feedingmentioning
confidence: 99%
“…When these two studies are considered together (Farrimond et al ), a number of suggestions can be made: firstly, since the observed effects of the non‐Δ 9 THC components of the extracts administered reduced hyperphagia when presented in one ratio and increased hyperphagia when presented in a different ratio, it is highly unlikely that the plant matter also present was responsible for these effects, given that its content did not change between the two tests. Secondly, it is possible that the pCBs present in both studies did not act in isolation such that more than one compound induced the observed effects.…”
Section: Cannabinoid‐mediated Effects Upon Feedingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these failed to demonstrate efficacy, in part due to dose‐limiting psychoactive side effects . In addition to Δ 9 ‐THC, there are now known to be over 100 other phytocannabinoids in C. sativa , the majority of which are non‐psychoactive, some of which have appetite‐modulating effects . We have recently shown that cannabigerol (CBG), a non‐psychoactive phytocannabinoid, increases food intake in healthy rats without eliciting neuromotor side effects .…”
Section: Introductionmentioning
confidence: 99%